41=-7(t-6)-15

Simple and best practice solution for 41=-7(t-6)-15 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 41=-7(t-6)-15 equation:



41=-7(t-6)-15
We move all terms to the left:
41-(-7(t-6)-15)=0
We calculate terms in parentheses: -(-7(t-6)-15), so:
-7(t-6)-15
We multiply parentheses
-7t+42-15
We add all the numbers together, and all the variables
-7t+27
Back to the equation:
-(-7t+27)
We get rid of parentheses
7t-27+41=0
We add all the numbers together, and all the variables
7t+14=0
We move all terms containing t to the left, all other terms to the right
7t=-14
t=-14/7
t=-2

See similar equations:

| 18/36=16/3x+11 | | P=5(10)-2x | | -29=3(b-2)+4 | | -10(-1)+3y=34 | | -5(t-7)+3=38 | | P=5(10-2x) | | -10x+3(-8x)=34 | | -2(d-11)-14=6 | | 7(-4)-3y=8 | | 12/x*12.2-100=0 | | 4(w-4)-10=6 | | -5(-2)+2y=-42 | | 6(-2)=y | | -2(u-4)=-16 | | -5x+2(6x)=-42 | | -45=5(q+1) | | x=-(4) | | -r-7r=40 | | -6(4+v)=18 | | 8x+10(4)=8 | | 32=4(1+a) | | -29=8u+19 | | -7b+3=-4b+b+5-2b | | 1.2=1.5^n | | 7(41)-8y=-41 | | 12=6(v-2) | | 16=-9q+7q | | 40=8(y+2) | | 3x/1.025^6+x(1.025)^8=2641.35 | | -x+(-5)=30 | | -(7y)+y=30 | | 2(b+3)=15 |

Equations solver categories